EXTEMPORANEOUS COMPOUNDING PRACTICE BY PHARMACISTS: A SYSTEMATIC REVIEW - Kristina, Susi Ari; Wiedyaningsih, Chairun; Widyakusuma, Niken Nur; Aditama, Hardika (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To identify the frequency and scope of extemporaneous compounding practice reported in community and hospital pharmacies. Methods: A systematic literature review was undertaken to identify the prevalence of extemporaneous compounding practice in community and hospital pharmacies, including the reasons of providing compounding services. Results: Nine studies were identified and evaluated in which extemporaneous products prepared by pharmacist could be identified. Most of the studies record that prevalence of extemporaneous compounding practice is very low (less than 5%). Prescribing of compounded medicines occurs more frequently in paediatrics and for special patients' need. The major types of extemporaneous compounding products were dermatological dosage forms and followed by oral solutions and oral suspensions. Reasons for providing compounding practice were to make a customised products that not available commercially and to provide full pharmaceutical care to patients. Issues about the stability of compounded products, accuracy in dose strength and lack of standardised protocol in extemporaneous compounding need to be addressed. Conclusion: Extemporaneous compounding practice are an essential part of pharmacist' competency. These unique skills need to be preserved and regulations that cover rationalised compounding practice is necessary.